2016
DOI: 10.1007/s10265-016-0830-3
|View full text |Cite
|
Sign up to set email alerts
|

Viola woosanensis, a recurrent spontaneous hybrid between V. ulleungdoensis and V. chaerophylloides (Violaceae) endemic to Ulleung Island, Korea

Abstract: Ulleung Island is an oceanic volcanic island in Korea, which has never been connected to the adjacent continent. Previous studies highlighted Ulleung Island as an excellent system to study the pattern and process of early stages of flowering plant evolutions on oceanic island. The predominant mode of speciation in flowering plants on Ulleung Island appears to be anagenesis. However, the potentially important role of hybrid speciation among incompletely reproductively isolated lineages cannot be ruled out. Viol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 80 publications
3
9
0
Order By: Relevance
“…For the chloroplast markers, we surveyed more than 30 chloroplast DNA (cpDNA) non-coding and coding regions to select variable regions among the populations of S. takesimensis (Shaw et al 2005(Shaw et al , 2007. Polymerase chain reaction (PCR) amplification was performed using the standard protocol of the Inclone™ Taq DNA polymerase Kit (Inclonebiotech Co., Yongin, Korea) with a final volume of 50 µl, as previously described in Gil and Kim (2016). To capture possible paralogous nrDNA ribotypes, we carried out three separate PCR reactions from different thermocyclers for each sample and pooled them together before the purification step.…”
Section: Dna Isolation Amplification and Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…For the chloroplast markers, we surveyed more than 30 chloroplast DNA (cpDNA) non-coding and coding regions to select variable regions among the populations of S. takesimensis (Shaw et al 2005(Shaw et al , 2007. Polymerase chain reaction (PCR) amplification was performed using the standard protocol of the Inclone™ Taq DNA polymerase Kit (Inclonebiotech Co., Yongin, Korea) with a final volume of 50 µl, as previously described in Gil and Kim (2016). To capture possible paralogous nrDNA ribotypes, we carried out three separate PCR reactions from different thermocyclers for each sample and pooled them together before the purification step.…”
Section: Dna Isolation Amplification and Sequencingmentioning
confidence: 99%
“…The island is very small with a total area of 73 km 2 , its highest peak rises up to 984 m, and it contains approximately 500 native vascular plant species, about 30-40 of which are endemic to the island (Hong et al 2002;Jung et al 2013;Sun et al 2014;Yang et al 2015). Although it was recently confirmed that some of the endemic species originated via hybridization (Gil and Kim 2016;Shin et al 2014), the predominant mode of generating the diversity of endemic plant lineages on Ulleung Island was considered anagenetic speciation. Several studies have confirmed the origin of endemic vascular plant species via anagenesis and have addressed the genetic consequences of anagenetic speciation (e.g., Pfosser et al 2002Pfosser et al , 2006Pfosser et al , 2011Takayama et al 2012Takayama et al , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Haplotype sharing and an almost equal distribution of these shared haplotypes could point to past hybridisation events between the two Viola species (Toyama et al . ; Gil & Kim ). Because V. reichenbachiana and V .…”
Section: Discussionmentioning
confidence: 99%
“…Korean Viola represents one of the most important angiosperm lineages, with 43-64 recognized taxa (Yoo and Jang, 2010), but little is known regarding the contribution of allopolyploidy in the speciation of phylogenetically and taxonomically complex groups. Of the numerous hybrid and polyploidy complexes, Viola woosanensis, endemic to Ulleung Island in Korea, has been suggested to be of hybrid origin involving other Ulleung Island endemic V. ulleungdoensis and East Asia-restricted V. chaerophylloides (Gil and Kim, 2016). As we assembled the plastomes of these Viola species to gain insights into the origin and evolution of Ulleung Island endemics, we discovered the absence of infA, rpl32, and rps16.…”
Section: Introductionmentioning
confidence: 93%